"You Cannot Trade What Is Not Yours": Indigenous Governance and the NAFTA Negotiations. Issue 2 (3rd April 2019) - Sarson, Leah
ABSTRACT: Contemporary International Relations scholars and practitioners generally recognize that substate governments affect the state's international affairs; however, there is less acceptance of Indigenous governments as global actors that meaningfully impact the state. After all, the expectation would be that central governments, with considerably more resources and power, would be unlikely to face a challenge from an Indigenous government. However, Indigenous governments are negotiating new relationships with foreign and domestic governments, forming economic development corporations, hiring private firms to raise capital, funding trade missions, and even opening offices in key international locales such as Beijing to engage in trade promotion and push investment opportunities in projects such as resource extraction. Applying paradiplomacy theory, which argues that International Relations cannot be properly explained absent the global affairs of substate governments, this article analyzes the effect of Indigenous peoples and governance in the Canada–US trade relationship. It specifically considers how Indigenous engagement in the global economy affects the bilateral trade regime, foreign direct investment, and cross-border trade. The driver for these analysis centers on demands for the inclusion of a so-called "Indigenous chapter" in the North American Free Trade Agreement renegotiations in 2017 and 2018.